RELATIONSHIP BETWEEN EMOTIONAL INTELLIGENCE AND SELF-LEADERSHIP IN ZAKAT INSTITUTIONS IN MALAYSIA - Abdul Halim, Anis Syamila; Abdul Ghani Azmi, Ilhaamie (Online Journal of Islamic Management and Finance (OJIMF), 2023)
Zakat institutions have been growing especially in Malaysia as one of the Islamic countries. Zakat institutions serve as Islamic organizations in handling everything that related to Zakat such as collection and distribution within the state in Malaysia. The image of Zakat employees is reflected in how they managed themselves especially in emotional intelligence. This research is conducted to study the relationship between self-leadership and emotional intelligence of Zakat employees in Malaysia. This quantitative study has collected 208 samples of Zakat employees from three states in Malaysia through online surveys. Descriptive analysis and inferential statistics were used via IBM Statistical Package for the Social Sciences (IBM SPSS) software. The findings showed that there is positive correlation between self-leadership and emotional intelligence (r= 0.776) of the Zakat employees. From the best knowledge of authors, this study is among the first conducted in Malaysia especially covering among Islamic organizations. This study contributes to future undertaking of Zakat organizations to improve especially self-leadership and emotional intelligence among its employees.